2021
DOI: 10.1108/jsocm-09-2019-0137
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how gamification influences consumers’ dietary preferences

Abstract: Purpose Nutritional disorders and unhealthy nutrition, which are recognised as the causes of many widespread health problems (overweight, obesity, diabetes, cardiovascular disease, cancer, etc.) have emerged as a significant problem that requires resolution. The purpose of this study is to influence dietary preferences and to reduce current health issues by using gamification as a social marketing tool. To this end, the decision-making processes affecting food choices in individuals based on calorific content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 161 publications
0
1
0
Order By: Relevance
“…This evidence leads the way in considering the relevance of some authors, regarding the theme, in the scientific panorama as pillars in specific matters and their works as a starting point for future research routes. In witness whereof, several authors referred to Deterding S.'s gamification definition [11,12] to identify the concept of design elements to be employed in user engagement strategies [66][67][68][69][70][71][72][73][74][75][76][77][78][79] and the application context of the non-gaming context [29,59,69,73,[80][81][82]. However, this represents a weakness of the research field, due the presence of other definitions capable of providing interesting types of identification of the gamification concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence leads the way in considering the relevance of some authors, regarding the theme, in the scientific panorama as pillars in specific matters and their works as a starting point for future research routes. In witness whereof, several authors referred to Deterding S.'s gamification definition [11,12] to identify the concept of design elements to be employed in user engagement strategies [66][67][68][69][70][71][72][73][74][75][76][77][78][79] and the application context of the non-gaming context [29,59,69,73,[80][81][82]. However, this represents a weakness of the research field, due the presence of other definitions capable of providing interesting types of identification of the gamification concept.…”
Section: Discussionmentioning
confidence: 99%
“…However, this represents a weakness of the research field, due the presence of other definitions capable of providing interesting types of identification of the gamification concept. For example, gamification is understood as a strategy or an approach [59,83,84], an emerging trend [57] or a set of activities or services [67,84,85] that are useful for providing learning, communication and interaction to the user in a fun and engaging atmosphere in order to enhance results and behaviours, providing a better user experience. Moreover, gamification is understood as an integration or supporting tool (i) to foster co-creation processes of, for example, a new kind of healthy food product as well as a form of product advertising [86,87]; (ii) to engage specific users such as consumers, children and farmers [56,[88][89][90][91][92]; (iii) to stimulate food behaviour change [29] and technology usage [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the game could lead to increased motivation to take informed actions by creating positive peer pressure (Lee et al , 2013). In the field of diet management, Ögel Aydın and Argan (2021) tested the efficacy of gamification in influencing dietary preferences when ordering food online. They compared gamified menus vs regular non-gamified menus and reported that the use of gamified menus can significantly influence users’ decisions towards choosing healthier foods when ordering online.…”
Section: What Constitutes a Transformative Gamification Service?mentioning
confidence: 99%